Kebijakan Energi Baru-terbarukan Serta Peluang Pemanfaatan Biogas dan Biomasa Limbah Pengolahan Kelapa Sawit untuk Pembangkit Tenaga Listrik Di Propinsi Riau - Eddon Mufrizon; Purwo Subekti (Jurnal APTEK, 2013)
This paper discusses the government's policy on the development of new energy-renewable and its relation to the utilization of palm oil waste in the form of biogas and biomass for power generation. Riau Province has a backup source of energy Biogas and Biomass from palm oil waste considerable. Biogas untapped in millers (MCC) reached 112MW, while the biomass of 905.8 MW. When this energy source utilized, can increase the electrification ratio, especially for rural areas (remote areas) reached 4.4% of the biogas and 36% of the biomass. Meanwhile, Electrification Ratio Riau Province in 2010 amounted to 43.27%, below the national average that has reached 65%. Development of Biogas PLTMG-sufficient financially beneficial to the period of return (payback period) for 6 years. Strategies needed to implement it through a few patterns involving PKS companies and / or investors and PT. PLN is facilitated by the Regional Government of intensive and consistent